2023
DOI: 10.1039/d2fo02364d
|View full text |Cite
|
Sign up to set email alerts
|

Ovotransferrin alleviated acute gastric mucosal injury in BALB/c mice caused by ethanol

Abstract: Acute gastric mucosal injury is a common gastrointestinal disorder, which influences patients’ life quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In recent years, hydrolysates of major egg proteins like ovalbumin, ovotransferrin, and lysozyme have been reported to have antioxidant properties. [45][46][47] However, for ovomucoid, research focused on its allergenicity, and seldom any attention has been paid to its antioxidant activity. This work demonstrates for the first time that after unfolding, glycation and simulated digestion, the ovomucoid peptides can possess increased antioxidant activity.…”
Section: Papermentioning
confidence: 99%
“…In recent years, hydrolysates of major egg proteins like ovalbumin, ovotransferrin, and lysozyme have been reported to have antioxidant properties. [45][46][47] However, for ovomucoid, research focused on its allergenicity, and seldom any attention has been paid to its antioxidant activity. This work demonstrates for the first time that after unfolding, glycation and simulated digestion, the ovomucoid peptides can possess increased antioxidant activity.…”
Section: Papermentioning
confidence: 99%
“…After the final gavage, the mice were fasted for 24 h to ensure complete digestion and absorption of gastric contents, with free access to water during this period. Except for the CK group, all other groups were given 75% ethanol (0.1 mL/20 g) by gavage to induce acute gastric mucosal injury, while the CK group received an equivalent amount of distilled water [22]. One hour after the gavage, the mice were euthanized by dislocating the cervical spine, and organs (liver, kidney, spleen, gastric) and serum were rapidly collected after enucleating the eyeballs and drawing blood from the neck dislocation site.…”
Section: Animals and Groupsmentioning
confidence: 99%
“…Our previous studies have found that OVT possesses antiinflammatory, antioxidant, and immunomodulatory activities. 22,23 However, the anti-inflammatory activity and mechanism of the OVT in gastric mucosa are still unclear. Additionally, the human normal gastric epithelial cell (GES-1) line immortalized by simian virus 40 (SV40) can mimic the primary gastric epithelium of adults.…”
Section: Introductionmentioning
confidence: 99%